The Implementation of Curriculum 2013 in English Language Teaching and Learning by English Teachers at SMA n 3 Kota Jambi Academic Year 2016/2017 - Novrianti Rumapea; Sri Marmoah; Yanti Ismiyati (Universitas Batanghari Jambi, 2017)
Abstract Curriculum is undoubtedly and inseparable part of education. The newly introduced and implemented one is called Curriculum 2013. Involving a “scientific approach”, this curriculum is expected to answer both the needs and the challenges to improve the quality of education in Indonesia.The teacher’s role is very necessary in the success of Curriculum 2013 implementation. If the teacher implements it well, the students with real good quality will be created as the objectives of Curriculum 2013. The objective of this study is to know the implementation of Curriculum 2013 by the English teachers in teaching learning planning, teaching learning process, and learning evaluation. The research used descriptive qualitative method. Data were collected through questionnaire and interview. Subject of this research were five English teachers. The research shows that the English teachers in SMA N 3 Kota Jambi have implemented the teaching learning planning especially in the arrangement of lesson plan and refers to the syllabus in accordance with the Curriculum 2013 despite some obstacles that they found. The teachers have implemented teaching learning process in accordance with the Curriculum 2013 development which included in pre-activity, main activity and post activity during the teaching and learning process. In learning evaluation, the English teachers performedquite well in accordance with Curriculum 2013. Nevertheless, some teachers find obstacles in the scoring criteria.Key Words: Implementation, Curriculum 2013, English language teaching and learning, English teachers